2014
DOI: 10.5966/sctm.2014-0109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Allogenic Implantation of Adipogenic Differentiated Adipose-Derived Stem Cells

Abstract: We recently reported that autologous adipogenic differentiated adipose-derived stem cells (ASCs) can potentially be used as an effective and safe therapy for soft-tissue regeneration. In the present study, we investigated whether adipogenic differentiated ASCs can be used for allogenic applications to enlarge their therapeutic use. The allogenic immune response of adipogenic differentiated ASCs was investigated by flow cytometry and mixed lymphocyte culture. To determine whether adipogenic differentiated ASCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Increasingly, however, in vivo studies report that allo-MSCs are not fully immune privileged and probably cause an immune response despite the immunosuppressive properties and low immunogenicity of MSCs being documented both in vivo and in vitro. Currently, different research groups have obtained inconsistent or even contradictory results on the therapeutic effects of allo-MSCs in various studies [ 18 21 ]. Therefore, the in vivo immunogenicity of allo-MSCs and the relationship between immunogenicity and their protective effects remains to be determined.…”
Section: Factors Influencing the Protective Effect Of Allo-mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, however, in vivo studies report that allo-MSCs are not fully immune privileged and probably cause an immune response despite the immunosuppressive properties and low immunogenicity of MSCs being documented both in vivo and in vitro. Currently, different research groups have obtained inconsistent or even contradictory results on the therapeutic effects of allo-MSCs in various studies [ 18 21 ]. Therefore, the in vivo immunogenicity of allo-MSCs and the relationship between immunogenicity and their protective effects remains to be determined.…”
Section: Factors Influencing the Protective Effect Of Allo-mscsmentioning
confidence: 99%
“…There are two types of topical administration: intralesional injection (e.g., intracranial, intracerebral, subcutaneous) and local vascular injection (e.g., superior vena cava, mesenteric blood vessels, coronary artery). Compared with systemic administration, topical administration routes may have a common advantage in that MSCs arrive directly at the target tissue with little loss during migration [ 18 , 22 ]. It was demonstrated that allo-MSCs loaded onto cancellous bone granules have a similar efficacy to auto-MSCs for bone regeneration in bone defect models [ 23 ].…”
Section: Factors Influencing the Protective Effect Of Allo-mscsmentioning
confidence: 99%
“…Adipose‐derived stromal cells (ASCs) isolated from adipose tissues in vitro have adipogenic (Kim, ), osteogenic (Gong, ), chondrogenic (Mellor, ), myogenic (Lee and Kemp, ), cardiomyogenic (Gwak, ), angiogenic (Mehrabani, ), epithelial (Nieto Miguel, ), and neurogenic (Safford, ) properties and remain these properties after serial passages (Zhu, ). And human adipose tissues are ubiquitous, abundance, rich in ASCs, and easy to obtain with little operative site morbidity and patient discomfort.…”
mentioning
confidence: 99%
“…In particular, ASCs express a low level of major histocompatibility complex (MHC) class I molecules and do not express MHC class II and costimulatory molecules, such as CD40, CD80 (B7-1), and CD86 (B7-2) [19][20][21]. Interestingly, also adipogenic-differentiated ASCs have no immunogenicity and are clinically safe [22]. Based on these properties, ASCs have generated great interest and are perceived as the most preferred cell type for tissue engineering and regenerative medicine [23].…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%